A Békésy audiometer with electronic signal level control and its application to psychoacoustical measurements - JAROSZEWSKI, Antoni; RAKOWSKI, Andrzej (Archives of Acoustics, 1976)
Improvements introduced in the new version of a Békésy automatic audiometer with electronic control of signal level are described, with some details of the separate circuits used.Examples of the uses of the new audiometer in threshold audiometry and some other applications are discussed.